解方程2x-5=3x-9时,移项正确的是().
A: 2x+3x=9+5
B: 2x-3x=-9+5
C: 2x-3x=9+5
D: 2x-3x=9-5
A: 2x+3x=9+5
B: 2x-3x=-9+5
C: 2x-3x=9+5
D: 2x-3x=9-5
举一反三
- 若集合A={x|-5<;x<;2},B={x|-3<;x<;3},则A∩B=( ) A: {x|-3<;x<;2} B: {x|-5<;x<;2} C: {x|-3<;x<;3} D: {x|-5<;x<;3}
- set1 = {x for x in range(10) if x%2!=0} print(set1) 以上代码的运行结果为? A: {1, 3, 5, 7, 9} B: {1, 3, 5, 7} C: {3, 5, 7, 9} D: {3, 5, 7}
- 已知E(X)=2, D(X)=3, 则E(X²)=( ). A: 5 B: 7 C: 9 D: 10
- set1 = {x for x in range(10) if x%2!=0} set1.remove(1) print(set1) 以上代码的运行结果为? A: {1, 3, 5, 7, 9} B: {1, 3, 5, 7} C: {3, 5, 7, 9} D: {3, 5, 7}
- 求方程组的解,取初值为(1,1,1)。[img=250x164]180333307ab8fde.jpg[/img] A: f=@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3];x=fsolve(f,[1,1,1],optimset('Display','off')) B: x=fsolve(@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3],[1,1,1]) C: f=@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3];x=fzero(f,[1,1,1]) D: x=fzero(@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3],[1,1,1])